Case Report: Invasive Cryptococcosis in French Guiana: Immune and Genetic Investigation in Six Non-HIV Patients - Goupil de Bouillé, Jeanne; Epelboin, Loïc; Henaff, Fanny; Migaud, Mélanie; Abboud, Philippe; Blanchet, Denis; Aznar, Christine; Djossou, Felix; Lortholary, Olivier; Elenga, Narcisse; Puel, Anne; Lanternier, Fanny; et al. (Frontiers in Immunology, 2022)
Objectives We describe the clinical, mycological, immunological, and genetic characteristics of six HIV-negative patients presenting with invasive cryptococcosis. Methods Patients with cryptococcosis without any of the classical risk factors, such as HIV infection, followed at Cayenne Hospital, were prospectively included. An immunologic and genetic assessment was performed. Results Five male patients and one female patient, 5 adults and one child, were investigated. All presented a neuromeningeal localization. Cryptococcus neoformans var. gattii and C. neoformans var. grubii were isolated in two and three patients, respectively, whereas one patient could not be investigated. Overall, we did not observe any global leukocyte defect. Two patients were found with high levels of circulating autoantibodies against Granulocyte macrophage-colony stimulating factor (GM-CSF), and none had detectable levels of autoantibodies against Interferon gamma (IFN-γ) Sequencing of STAT1 exons and flanking regions performed for four patients was wild type. Conclusion To better understand cryptococcosis in patients with cryptococcosis but otherwise healthy, further explorations are needed with repeated immune checkups and strain virulence studies.